Weak gravitational lensing - Bartelmann, Matthias; Schneider, Peter (Arxiv, 2008)
We review theory and applications of weak gravitational lensing. After summarising Friedmann-Lemaitre cosmological models, we present the formalism of gravitational lensing and light propagation in arbitrary space-times. We discuss how weak-lensing effects can be measured. The formalism is then applied to reconstructions of galaxy-cluster mass distributions, gravitational lensing by large-scale matter distributions, QSO-galaxy correlations induced by weak lensing, lensing of galaxies by galaxies, and weak lensing of the cosmic microwave background. Contents: Introduction - Cosmological Background - Gravitational Light Deflection - Principles of Weak Gravitational Lensing - Weak Lensing by Galaxy Clusters - Weak Cosmological Lensing - QSO Magnification Bias and Large-Scale Structure - Galaxy-Galaxy Lensing - The Impact of Weak Gravitational Lensing on the Microwave Background Radiation - Summary and Outlook